Evaluation of immunogenicity, safety and breakthrough following administration of live attenuated varicella vaccine in two doses three months apart regimen in Indian children - Monjori Mitra; Jaydeep Chowdhury; Surupa Basu; Partha Pratim Halder; Mallar Mukherjee; Archana Karadkhele; Gaurav Puppalwar; Rishi Jain (SAGE Publishing, 2020)
Background: In India, where varicella outbreaks are reported at a younger age, a two-dose vaccine schedule administered at an early age could be highly efficacious in preventing varicella infection. The aim of this study was to evaluate the immunogenicity and safety of live attenuated varicella vaccine (VR 795 Oka strain) in a two-dose, 3 months apart regimen. Methodology: Healthy children (⩾ 12 months and ⩽12 years; mean age: 4.4 years) of either sex were included. Geometric mean titers (GMT) were measured at baseline and 28 days post first- and second-dose, and seroprotection rates were measured 28 days post first and second dose. The incidence of breakthrough (BT) infections post vaccination was determined from 42 days post first and second dose of vaccine up to 12 months. Adverse events (AEs) were monitored and recorded throughout the study period. Results: Of 305 subjects enrolled, 217 were seronegative. The seroconversion rate (a change from a seronegative to a seropositive condition) was 93.3% post first-dose and 100% post two-doses. High levels (9 times) of GMT were reported since post first-dose to post second-dose in children aged 12-18 months, 18-60 months (99.43%); and in and above 60 months (99.02%). The extent of rise of anti-VZV IgG antibody titer post 28 days of first-dose at two-fold, three-fold and four-fold rise was 93.39%, 90.56% and 80.66%, respectively and 100% 4-fold rise post second-dose. A single case, a day after the first-dose of vaccination of mild BT infection, was observed after close contact with a severe case. AEs were mild and none of the serious AEs were related to the study drug. Conclusion: The two-dose schedule of varicella vaccine was safe and immunogenic when given 3 months apart. However, further comparative studies and follow up for both dosing schedules are needed to validate the advantage of early dosing.